The feral detective : a novel [compact disc, unabridged] - Lethem, Jonathan (Harper Collins Publishers, 2018)
Phoebe Siegler first meets Charles Heist in a shabby trailer on the eastern edge of Los Angeles. She's looking for her friend's missing daughter, Arabella, and hires Heist to help. Heist intrigues the sarcastic and garrulous Phoebe. Reluctantly, he agrees to help. The unlikely pair navigate the enclaves of desert-dwelling vagabonds and find that Arabella is in serious trouble, caught in the middle of a violent standoff that only Heist, mysteriously, can end.